Verification of CENDL-3.2 and ENDF/B-VIII.0 Evaluated Nuclear Data Library on HTR-10 Benchmark - Huang, Tianyi; Li, Zeguang; Jiang, Shihang; Wang, Kan (Frontiers in Energy Research, 2022)
CENDL-3.2 and ENDF/B-VIII.0 referring to the latest version of CENDL and ENDF/B, respectively, evaluated nuclear data library. To examine the applicability the libraries to high-temperature reactors (HTRs), the HTR-10 benchmark calculations are conducted by adopting CENDL-3.2, ENDF/B-VIII.0, and ENDF/B-VII.1 library. The calculated results are compared with the experimental results. As indicated from the comparison, the results of ENDF/B-VIII.0 show the optimal consistency with the experimental results, and CENDL-3.2 outperforms ENDF/B-VII.1. A semi-quantitative analysis method, on the basis of the sensitivity result, is employed to assess the effect of the cross-section change to keff. As revealed from the further calculations and analyses, the difference between cross-sections of C-12 (n, γ) channel primarily causes the inconsistent performance of CENDL-3.2 and ENDF/B-VIII.0 on the benchmark.